Factors Responsible for Non Compliance to Treatment in Pulmonary Tuberculosis - Muhammad Nadeem , Usman Zaffar , Muhammad Imran Ullah , Muhammad Rameez Khalid ,Shahid Iqbal Sheikh , Syed Irfan Ahmed, (Journal of Rawalpindi Medical College, 2014)
Background: To determine factors responsible for non compliance to anti-tuberculous treatment. Methods: In this cross sectional observational study patients (n=170) with history of non compliance to anti-tuberculous treatment were interviewed to get the relevant information. Results: The mean age of patients was 39.5 + 16.7 years ranging from 14 to 75. Out of 170 study cases, 23.5% were non compliant due to lack of proper guidance, 13% stopped treatment due to side effects of drugs, 9.4% were going to hakims and 8.2% had social reasons for non-compliance. Complicated treatment regimen was a confounding variable in 6.4%. Conclusion: Main factors responsible for non compliance were patients thinking themselves cured and lack of proper guidance.